The power of natural products against bacteria caused the acne - Juman Khaleel Al-Sabbagh,; Nawras Majeed Al-Khafaji,; Rana Abdulameer Jawad,; Ali Jasim Al-Nuaimi, (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the inhibitory effect of lemon, green tea and Shea butter on the bacteria isolated from patients with acne. Method: This Experimental study was conducted at the Microbiology laboratory of the Department of Veterinary Medicine, Kerbala University, Iraq. From February-March/2022. Simple random sampling was used to collect the samples. The culture media was incubated aerobically for 24 hours at 37°C. Lemon, green tea and Shea butter was used to test antimicrobial activity against the isolated bacteria. Antibiotics disks of tetracyclin, methicillin, azithromycin and clarithromycin were used to compare the effect of natural products. Data was analysed using SPSS. Results: There were 50 subjects (35 males and 15 females) included, with mean age 21±3 years (range: 19-24 years). Among the 50 swabs, 26(52%) different microorganisms were isolated. All the isolates show 100% sensitivity against lemon, and 83.3% against green tea, while all the isolates were resistant to Shea butter. The sensitivity of isolates towards the antibiotics used ranged 16.6-83.3%. Conclusion: While lemon and green tea could play a crucial role against different types of bacteria that caused acne, Shea butter had no role to play in this regard. Key Words: Clarithromycin, Azithromycin, Methicillin, Tea, Bacteria, Acne Vulgaris